취약계층 식품지원제도의 운영 실태 분석 - 이계임 (한국농촌경제연구원, 2013)
This study aims to review the operation status of the food support system and to suggest ways to further invigorate government food aid programs aimed at ensuring sustainable food supply to the vulnerable people. The government food aid programs should be aimed at ensuring sustainable food supply to the nation while striving to build connections to local agricultural industry and food producers in order to enhance access to safe and fresh foods. Program accessibility and adoptability by the needy should be thoroughly considered and the efficient operation of the food aid policies should be ensured through the foundation of close links among related parties. New food aid programs need to be initiated toward selected groups of people who need food support due to their insufficient food consumption and nutritional intake.